2015
DOI: 10.1142/s1793984415500014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Local Anesthetics on Human Mesenchymal Stromal Cell Secretion

Abstract: Anti-fibrotic and tissue regenerative mesenchymal stromal cell (MSC) properties are largely mediated by secreted cytokines and growth factors. MSCs are implanted to augment joint cartilage replacement and to treat diabetic ulcers and burn injuries simultaneously with local anesthetics, which reduce pain. However, the effect of anesthetics on therapeutic human MSC secretory function has not been evaluated. In order to assess the effect of local anesthetics on the MSC secretome, a panel of four anesthetics with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 42 publications
3
30
1
Order By: Relevance
“…The MSC-alginate constructs so generated, expressed immunomodulatory capacity. This confirms the recent studies of Stucky and co-workers, demonstrating an inhibition of neuro-inflammation by MSCs that were encapsulated in alginate for 1 d, and Gray and coworkers, demonstrating secretion of factors in reaction to inflammatory cytokines after 2 d of encapsulation in alginate (Gray et al, 2015;Stucky et al, 2015). We demonstrate, in this study, that MSC encapsulated in alginate can inhibit T cell proliferation.…”
Section: Mjc Leijs Et Al Encapsulation Of Mscs In Alginatesupporting
confidence: 89%
“…The MSC-alginate constructs so generated, expressed immunomodulatory capacity. This confirms the recent studies of Stucky and co-workers, demonstrating an inhibition of neuro-inflammation by MSCs that were encapsulated in alginate for 1 d, and Gray and coworkers, demonstrating secretion of factors in reaction to inflammatory cytokines after 2 d of encapsulation in alginate (Gray et al, 2015;Stucky et al, 2015). We demonstrate, in this study, that MSC encapsulated in alginate can inhibit T cell proliferation.…”
Section: Mjc Leijs Et Al Encapsulation Of Mscs In Alginatesupporting
confidence: 89%
“…7 In addition, we previously observed that a high concentration (1 mM) of lidocaine or bupivacaine resulted in decreased constitutive secretion of PGE2 by monolayer MSCs. 18 Therefore, we next characterized the effect of LAs on PGE2 levels in the co-culture of macrophages and MSCs. Levels of PGE2 detected from macrophages alone with and without LAs were low relative to co-cultures of macrophages and MSCs, suggesting that the MSCs were the main source of PGE2 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…For comparative purposes, LA and LPS concentrations were selected based on previous in vitro studies performed by our group and others. 6, 7, 15, 18-23 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations